2002
DOI: 10.1152/ajpendo.00225.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in in vitro glyceride synthesis in subcutaneous and omental adipose tissue

Abstract: Considerable evidence suggests that there are ethnic differences in lipid metabolism between African American and Caucasian women, which may result in increased synthesis of fat in adipose tissue. The purpose of this study was to measure the in vitro rates of [14C]glucose incorporation into the glyceride-glycerol backbone of triglycerides (TG) and diglycerides (DG) in abdominal subcutaneous (SAT) and omental adipose tissue (OAT). Morbidly obese [African American (n = 15): body mass index (BMI) = 45 +/- 2.3; Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…This indicates that there could be modulators of lipoprotein metabolism involved that are related to visceral fat, which may result in a different expression of lipid phenotype. Indeed, Despres et al (2000) found higher lipoprotein lipase and lower hepatic lipase activities in African-American than in white women and Bower et al (2002) showed that African-American women have an increased capacity to synthesize locally TG in omental adipose tissue compared with Caucasian women. In African Americans, the relationship between BMI and waist circumference/visceral fat with assessment of computed tomography scanning (L4 protocol) is less than in white American women (Carroll et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that there could be modulators of lipoprotein metabolism involved that are related to visceral fat, which may result in a different expression of lipid phenotype. Indeed, Despres et al (2000) found higher lipoprotein lipase and lower hepatic lipase activities in African-American than in white women and Bower et al (2002) showed that African-American women have an increased capacity to synthesize locally TG in omental adipose tissue compared with Caucasian women. In African Americans, the relationship between BMI and waist circumference/visceral fat with assessment of computed tomography scanning (L4 protocol) is less than in white American women (Carroll et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the homogeneity of our study group on socioeconomic factors is a benefit because it reduces the likelihood of confounding by these factors. Future studies should examine whether these observations hold true in women and other racial populations as there are clear sex and racial differences in fat distribution (19) and adipocyte metabolism in vitro (20). Further, studies should investigate whether this pattern of association remains true with abdominal adipose tissue changes over time or whether the measurement site influences the relationship between changes in abdominal adipose tissue and obesity-related metabolic risk factors to determine the optimal landmark for the quantification of abdominal adiposity.…”
Section: Statistical Analysesmentioning
confidence: 98%
“…In a previous study (8), we reported differences in de novo triglyceride (TG) synthesis by adipose tissue preparations from AAW and CAW. We found no differences in the rate of synthesis of either TG or diglyceride (DG) in subcutaneous adipose tissue of the two groups of women.…”
mentioning
confidence: 99%